1999
DOI: 10.1093/bja/83.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop control of propofol anaesthesia

Abstract: We describe the use of a closed-loop system to control depth of propofol anaesthesia automatically. We used the auditory evoked potential index (AEPindex) as the input signal of this system to validate it as a true measure of depth of anaesthesia. Auditory evoked potentials were acquired and processed in real time to provide the AEPindex. The AEPindex was used in a proportional integral (PI) controller to determine the target blood concentration of propofol required to induce and maintain general anaesthesia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 35 publications
0
55
0
2
Order By: Relevance
“…As explained earlier in this chapter, concepts of TCI were applied to decrease the complexity of the PI controller. Accurate control was observed in most of the patients [14].…”
Section: Examples Of Closed-loop Drug Administrationmentioning
confidence: 85%
See 1 more Smart Citation
“…As explained earlier in this chapter, concepts of TCI were applied to decrease the complexity of the PI controller. Accurate control was observed in most of the patients [14].…”
Section: Examples Of Closed-loop Drug Administrationmentioning
confidence: 85%
“…Aside from BIS, State and Response Entropy (M-entropy, GE Healthcare, Helsinki, Finland), two spectral entropy parameters based on the irregularity in the EEG have been used recently to measure hypnotic drug effect during closed-loop administration [11-13 • ]. One research group has tested auditory evoked potentials, more specific the mid-latency auditory evoked potential (MLAEP) as controlled variable for closed-loop control of propofol administration [14,15]. One of the major challenges when using a surrogate measure is the delay in the system, which adds complexity to the controller.…”
Section: Pharmacokinetic-dynamic Closed-loop Systemsmentioning
confidence: 99%
“…It soon became clear that control of anesthesia poses a manifold of challenges, with multivariable characteristics (Zbinden et al;1995), time delay between drug administration and the clinical effect which can lead to system oscillations , different dynamics depending on anesthetics substances (Absalom and Struys; and stability problems (Asbury;1997). Further investigations proved Propofol to be an anesthetic tackled well in control problems (Kenny and Mantzaridis;, while recent studies showed that the control performance may also depend on the controlled variable (Ting et al;.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of solutions have been developed to resolve these problems, including the use of pharmacokinetic models to account for the time varying relationship between dose and effect-site concentration, adaptive controllers, or fuzzy logic to account for differences in sensitivity. [7][8][9][10][11] Thus, engineering solutions have been developed for the automated control of a biological system, and we have at least one component of anesthesia we can place under automated control. Hemmerling et al, like several previous authors, demonstrate the use of an automated closed-loop system to administer propofol to maintain BIS within a narrower band.…”
mentioning
confidence: 99%
“…Plusieurs solutions ont vu le jour pour résoudre ces problèmes, notamment l'utilisation de modèles pharmacocinétiques qui tiennent compte de la relation variant dans le temps entre la dose et la concentration au site effecteur, des contrôles adaptatifs, ou la logique de l'incertain pour tenir compte des différences de sensibilité. [7][8][9][10][11] Dès lors, des solutions techniques ont été mises au point pour la surveillance automatisée d'un système biologique, et au moins une composante de l'anesthésie peut être placée sous surveillance automatisée. Hemmerling et coll., tout comme plusieurs auteurs avant eux, illustrent l'utilisation d'un système automatisé en boucle fermée pour l'administration de propofol afin de maintenir le BIS dans une marge plus étroite.…”
unclassified